Ways of spectating: unravelling spectator participation in Kinect play - Tekin, Burak S.; Reeves, Stuart (ACM, 2017)
We explore spectating on video game play as an interactional and participatory activity. Drawing on a corpus of video recordings capturing 'naturally occurring' Kinect gaming within home settings, we detail how the analytic 'work' of spectating is interactionally accomplished as a matter of collaborative action with players and engagement in the game. We examine: spectators supporting players with continuous 'scaffolding'; spectators critiquing player technique during and between moments of play; spectators recognising and complimenting competent player conduct; and spectators reflecting on prior play to build instructions for the player. From this we draw out a number of points that shift the conversation in HCI about 'the spectator' towards understanding and designing for spectating as an interactional activity; that is, sequentially ordered and temporally coordinated. We also discuss bodily conduct and the particular ways of 'seeing' involved in spectating, and conclude with remarks on conceptual and design implications for HCI.